2015
DOI: 10.1161/atvbaha.114.305064
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Melanocortin 1 Receptor Signaling Predisposes to Vascular Endothelial Dysfunction and Increased Arterial Stiffness in Mice and Humans

Abstract: Objective— The melanocortin 1 receptor (MC1-R) is expressed by vascular endothelial cells and shown to enhance nitric oxide (NO) availability and vasodilator function on pharmacological stimulation. However, the physiological role of MC1-R in the endothelium and its contribution to vascular homeostasis remain unresolved. We investigated whether a lack of functional MC1-R signaling carries a phenotype with predisposition to vascular abnormalities. Approach and Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In the aorta of recessive yellow mice deficient in MC1 signalling, contractile capacity and NO‐dependent relaxations are impaired and arterial stiffness is increased (Rinne et al . ). In addition, humans with weak MC1 function exhibit reduced flow‐mediated dilatations and increased arterial stiffness (Rinne et al .…”
Section: Nitric Oxidementioning
confidence: 97%
See 1 more Smart Citation
“…In the aorta of recessive yellow mice deficient in MC1 signalling, contractile capacity and NO‐dependent relaxations are impaired and arterial stiffness is increased (Rinne et al . ). In addition, humans with weak MC1 function exhibit reduced flow‐mediated dilatations and increased arterial stiffness (Rinne et al .…”
Section: Nitric Oxidementioning
confidence: 97%
“…In addition, humans with weak MC1 function exhibit reduced flow‐mediated dilatations and increased arterial stiffness (Rinne et al . ). These observations suggest a chronic physiological endothelial protective role of the hormone.…”
Section: Nitric Oxidementioning
confidence: 97%
“…Several previous studies showed that the melanocortin system mediates inflammation and plays a role in sepsis. In an in vivo study, mice with defective MC1R signaling had more severe vascular dysfunction in response to lipopolysaccharide (LPS) than did wild-type mice(23). In another study, mice treated with α-MSH had less liver damage in response to LPS compared to untreated mice, an effect that was mediated by decreased leukocyte infiltration and cytokine accumulation(24).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others showed that alpha-MSH and its analogue, melanotan 2, evoke anti-inflammatory and vasoactive effects both in endothelial cells and in a mouse model of atherosclerosis (Rinne et al 2014, Yang et al 2015. On the other hand, deficient MC1R function disturbs the vascular endothelial function both in mice and humans (Rinne et al 2015). The vasoprotective effects arise from the augmentation of nitric oxide availability (Davignon & Ganz 2004, Rinne et al 2013, whereas the alleviation of inflammation stems from the inhibition of nuclear factor kappa B-driven inflammation (Manna & Aggarwal 1998, Yang et al 2015.…”
Section: Introductionmentioning
confidence: 99%